Insubmissas mulheres negras: racismo institucional e cotidiano na escrevivência de uma servidora pública negra - Almeida, Rosangela Araujo (2024)
This essay carries out a study on trajectories, experiences, and collective memory as a way of approaching critical reality of a working class daily life. I describe the history of my black northeastern migrant family, recovering my ancestry and experiences of people from the southwest region of the State of Bahia, workers in rural areas contributing to the epistemic erasure of the real history of a black population. This particular history was articulated with Brazilian social formation (Moura, 2019) which, after 1888, abolished slavery in Brazil, however, this did not promote citizenship for everyone. By triggering the memory of black women, many aspects of structural and institutional racism were rescued and revealed (Almeida 2019), which, through the use of prejudice and racial discrimination, consolidates in our society a racial division between who are considered lower class (blackness) and those who are considered upper class (whiteness). Also, through the concept of writing (Conceição Evaristo, 2020) and its epistemological assumptions, I present my condition being a black woman who is similar to many other black women in São Paulo society, bringing elements that identify everyday racism (Grada Kilomba, 2019) a problem that intersects between class, race and gender. The research has a central focus on work, and to this end, we present the results and analyzes of interviews narrated by black public servants from São Paulo City Hall, who, like me, experience and recognize institutional racism in occupational spaces as a method of social domination separating women, subjects of political and social rights of participation in relationships and work processes by distinction of their races. We were able to recover ourselves from those trajectories of workplace violence, the racialization caused by stigmas and stereotypes affected us, leading to a lot of suffering and trauma to the extent that left our bodies segregated within institutional relationships and caused mental exhaustion that altered the course of our lives